Upregulation of lncRNA147410.3 in the Brain of Mice With Chronic Toxoplasma Infection Promoted Microglia Apoptosis by Regulating Hoxb3 - Wang, Yongliang; Han, Ruxia; Xu, Zhejun; Sun, Xiahui; Zhou, Chunxue; Han, Bing; He, Shenyi; Cong, Hua (Frontiers in Cellular Neuroscience, 2021)
T. gondii is neurotropic and affects the function of nerve cells, while the mechanism is unclear. lncRNAs are abundantly enriched in the brain and participate in the delicate regulation of the central nervous system (CNS) development. However, whether these lncRNAs are involved in the regulation of microglia activation during the process of T. gondii infection is largely unknown. In this study, the upregulation of a novel lncRNA147410.3(ENSMUST00000147410.3) was identified as a key factor to influence this process. The target gene of lncRNA147410.3 was predicted and identified as Hoxb3. The localization of lncRNA147410.3 in the brain and cells was proved in the nucleus of neuroglia through FISH assay. Furthermore, the function of lncRNA147410.3 on neuronal cell was confirmed that lncRNA147410.3 could affect proliferation, differentiation and apoptosis of microglia by positively regulating Hoxb3. Thus, our study explored the modulatory action of lncRNA147410.3 in T. gondii infected mouse brain, providing a scientific basis for using lncRNA147410.3 as a therapeutic target to treat neurological disorder induced by T. gondii.